The role of "The Power of Mama" in addressing fires and forest degradation in Ketapang, Indonesia - Silitonga, Derina Faslig; AR, Akmal Maulana (Jurnal Ilmiah Hubungan Internasional, 2024)
In recent years, the destruction of forests, which can take many forms including deforestation and forest fires, has emerged as a major concern worldwide, and Indonesia is no exception. The deforestation rate in Indonesia is rising annually due to a number of factors, including decentralization and illegal land conversion. Kalimantan, known as the "lungs of the world," is the most impacted area, accounting for 51% of total tree cover loss between 2001 and 2022. This situation is alarming as it undermines the sustainability of the flora and fauna ecosystem and directly affects global warming. The government has intensified its efforts to prevent and manage forest fires, working in collaboration with businesses and non-governmental organizations (NGOs) like Greenpeace to reduce the risk of forest damage. In addition to these efforts, a protection initiative by a group of women in Ketapang, West Kalimantan, has gained public attention. Known as The Power of Mama, this group, as the one most affected by forest fires, undertakes heroic effortsto stop forest destruction. This research aims to examine the impact of The Power of Mama on forest degradation and fire management in Ketapang, West Kalimantan. Using a nonviolence approach that emphasizes alternative strategies and tactics leading away from violence, this study demonstrates the long-term positive impact of The Power of Mama through patrols, outreach, counselling, and third-party intervention in managing forest damage and fires. Furthermore,using qualitative methods and focusing on secondary data collection, this research reveals several challenges encountered by The Power of Mama in implementing its actions. Despite these challenges, The Power of Mama's nonviolent strategies and efforts have achieved widespread recognition and have positively impacted sustainability. This is particularly evident in the recognition that women are not only victims of environmental degradation but also play a significant role in environmental protection. Keywords: Non-violence; The Power of Mama; forest destruction; forest fires; women community